ANALISIS JABATAN PADA BAGIAN TATA USAHA (STUDI KASUS UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG) - Hatii, Amelia Tuffa; Sabur, Ambuy; Wahab, Andi Yustira (Universitas Islam Syekh Yusuf, 2022)
Job Analysis in the Administrative Section of the Sheikh Yusuf Islamic University Case Study This research was conducted at the Sheikh Yusuf Islamic University Tangerang. This study aims to determine the extent of Administrative Positions in the Faculty of Economics, FKIP, Postgraduate Program. This research uses Observation, Interview, and Documentation. In the case study research, Spadley did not use the term population, but called it